Circulating programmed death-1 as a marker for sustained high hepatitis B viral load and risk of hepatocellular carcinoma. - Hsiang-Yun Cheng; Pei-Jen Kang; Ya-Hui Chuang; Ya-Hui Wang; Meng-Chin Jan; Chih-Feng Wu; Chih-Lin Lin; Chun-Jen Liu; Yun-Fan Liaw; Shi-Ming Lin; Pei-Jer Chen; Shou-Dong Lee; et al. (PLoS ONE, 2014)
Objective Recent evidence indicates a crucial role of the immunoinhibitory receptor programmed death-1 (PD-1) in enforcing T-cell dysfunction during chronic viral infection and cancer. We assessed the impact of circulating soluble PD-1 (sPD-1) levels on long-term dynamics of hepatitis B virus (HBV) load and hepatocellular carcinoma (HCC) risk. Methods In a case-cohort study on longitudinal analysis of viral load within a cohort of 2903 men chronically infected with HBV, followed up from baseline (1989-1992) through 2010, we determined sPD-1 levels in baseline plasma with enzyme-linked immunosorbent assay from 126 men who subsequently developed HCC and 1155 men who did not develop HCC. To evaluate whether patients' characteristics involved the use of sPD-1 as a biomarker, sPD-1 was also tested in 614 newly-diagnosed patients with HBV-related HCC recruited from a multicenter study for comparison with the 1155 noncases in the case-cohort study. Results Plasma quartile levels of sPD-1 were positively associated with HCC risk for men in the case-cohort analysis (vs. quartile 1: adjusted odds ratios [95% confidence intervals] for quartile 2-quartile 4 were 1.51 [0.75-3.03], 2.15 [1.12-4.13], and 2.29 [1.20-4.38], respectively), and in the case-control study regardless of age-of-onset and clinical stage. Furthermore, we found longitudinal effect of elevated sPD-1 levels to maintain higher viral load for 4 or more years, with greater and more prolonged effect among HBV genotype C- vs. non-C-infected participants. High levels of viral load and sPD-1 (vs. absence of both) was associated with a 6.29-fold increase in risk of HCC, and combining both conditions with HBV genotype C yielded an odds ratio of 30.47 with significant additive interaction (relative excess risk due to interaction: 27.08 [95% confidence interval = 8.76-45.41]). Conclusions Our data suggest plasma sPD-1 as an important immune-related marker for assessment of HBV activity and HCC risk.